Assessement Of International Focus And Discourse On Antimicrobial Resistance (AMR) And Influence On Local Decision-Making On Amr In Ghana - Darfoor, J. (University of Ghana, 2017)
BACKGROUND: Antimicrobial resistance (AMR) is known to result in 700,000 deaths each year worldwide, mostly in low and middle income countries. Currently, Ghana faces a double disease burden from communicable and non-communicable diseases, coupled with poor monitoring of antibiotic use and weak regulatory systems. There is also a lack of capacity to link results of laboratory diagnostic tests to sale of medicines as well as uncontrolled veterinary use of antibiotics, compounding the problem. Discussions on AMR on the international stage have been ongoing since 1998 and yet countries have only recently begun to take action to contain AMR. OBJECTIVES: The aim of this study was to assess how International antimicrobial resistance (AMR) discourse-influences local policies and decisions on AMR in Ghana. METHOD: This was a descriptive cross sectional study assessing local AMR discourse and policies in relation to international discourse, as well as describes the decision –making process on AMR in Ghana. This was done by key informants’ interviews of purposively sampled key informants of the antimicrobial technical working group, using an interview guide. Documents reviews were done to supplement key informant interviews. RESULTS: The draft antimicrobial resistance policy for Ghana followed international discourse and was similar to the global action plan on antimicrobial resistance from the World Health Organization (WHO). It had five key overarching elements similar to that of the global action plan. The study also found that international discourse influenced the content, policy-formulation and decision-making process of Ghana’s draft policy as did other factors like political situation, local situation and local process-drivers CONCLUSION: Policy decisions are not only influenced by international discourse but the ability of the key players and policy formulators to understand and interpret what international discourse seeks to achieve and contextualize it to local prevailing country situations, the prevailing health systems and capacity for implementation of actions from international discourse. Also, political commitment is key however, the leadership that drives the policy formulation process or the ‘local champion’ with subject-matter exposure and ability to demystify international discourse to in-country stakeholders and rally support is what moves the process forward.
Thesis (MPH)
Keywords: Assessement; International Focus; Antimicrobial Resistance (AMR); Local Decision-Making